Short-Term Effects of a Ready-to-Drink Pre-Workout Beverage on Exercise Performance and Recovery - Collins, P. Blaise (Nutrients, 2017)
In a double-blind, randomized and crossover manner, 25 resistance-trained participants ingested a placebo (PLA) beverage containing 12 g of dextrose and a beverage (RTD) containing caffeine (200 mg), β-alanine (2.1 g), arginine nitrate (1.3 g), niacin (65 mg), folic acid (325 mcg), and Vitamin B12 (45 mcg) for 7-days, separated by a 7–10-day. On day 1 and 6, participants donated a fasting blood sample and completed a side-effects questionnaire (SEQ), hemodynamic challenge test, 1-RM and muscular endurance tests (3 × 10 repetitions at 70% of 1-RM with the last set to failure on the bench press (BP) and leg press (LP)) followed by ingesting the assigned beverage. After 15 min, participants repeated the hemodynamic test, 1-RM tests, and performed a repetition to fatigue (RtF) test at 70% of 1-RM, followed by completing the SEQ. On day 2 and 7, participants donated a fasting blood sample, completed the SEQ, ingested the assigned beverage, rested 30 min, and performed a 4 km cycling time-trial (TT). Data were analyzed by univariate, multivariate, and repeated measures general linear models (GLM), adjusted for gender and relative caffeine intake. Data are presented as mean change (95% CI). An overall multivariate time × treatment interaction was observed on strength performance variables (p = 0.01). Acute RTD ingestion better maintained LP 1-RM (PLA: −0.285 (−0.49, −0.08); RTD: 0.23 (−0.50, 0.18) kg/kg(FFM), p = 0.30); increased LP RtF (PLA: −2.60 (−6.8, 1.6); RTD: 4.00 (−0.2, 8.2) repetitions, p = 0.031); increased BP lifting volume (PLA: 0.001 (−0.13, 0.16); RTD: 0.03 (0.02, 0.04) kg/kg(FFM), p = 0.007); and, increased total lifting volume (PLA: −13.12 (−36.9, 10.5); RTD: 21.06 (−2.7, 44.8) kg/kg(FFM), p = 0.046). Short-term RTD ingestion maintained baseline LP 1-RM (PLA: −0.412 (−0.08, −0.07); RTD: 0.16 (−0.50, 0.18) kg/kg(FFM), p = 0.30); LP RtF (PLA: 0.12 (−3.0, 3.2); RTD: 3.6 (0.5, 6.7) repetitions, p = 0.116); and, LP lifting volume (PLA: 3.64 (−8.8, 16.1); RTD: 16.25 (3.8, 28.7) kg/kg(FFM), p = 0.157) to a greater degree than PLA. No significant differences were observed between treatments in cycling TT performance, hemodynamic assessment, fasting blood panels, or self-reported side effects.